Open Judicial Politics - Solberg, Rorie Spill; Diascro, Jennifer Segal; Waltenburg, Eric (Open textbook library., 2020)
The impetus for this volume was a multitude of conversations regarding pedagogy and teaching related to our judicial process courses. Based on these conversations, we identified four main threads or needs of our colleagues: First, many of us bring or want to bring more “political science” into our classes, though we also want to avoid the high costs of reinventing successful existing courses to do so. Second, our programs all require a political methodology course, and we want to reinforce those lessons in our substantive courses. We want to encourage our students’ understanding of how to read and understand research studies as well as how to craft their own research questions. Third, we want to keep our courses as current as possible. And fourth, we wanted to find a way to bring the cost of our courses down, as we see so many students struggle with the high costs of a college degree. This volume (as well as any future editions) addresses each of these concerns. Open Judicial Politics is a compilation of new and original research in judicial politics written specifically for the undergraduate audience, thus providing accessible examples of political science research that also address some of the more current concerns and controversies in our field. Additionally, every article is accompanied by some type of classroom activity—from basic discussion questions to full-blown simulations—that makes it easier for instructors to adapt the material to their courses and enhance classes with interactives. The chapters of the volume generally follow the well-worn path of most textbooks of judicial politics, making the volume an easy companion for adoption, and the material should fit seamlessly into the preestablished structures of most courses. Finally, the volume is an open-source resource, and adoption of the text adds no cost for our students. Whether one uses one or ten articles, the cost remains nil. This volume includes twenty-two original contributions that we have grouped into nine parts. The studies cover the breadth and scope of the field of judicial politics, with attention to appellate and trial courts, national high courts and intermediate appellate courts, and US courts and their international counterparts, thus providing a large range of materials to complement any judicial process course or text. We are especially pleased that undergraduate students played key roles in the creation of several of these studies, performing data collection and analysis as well as complete authorship from stem to stern. For the second edition, we have added fifteen articles that continue to illustrate key concepts and aspects of judicial politics, following the same formula of empirical research tailored to an undergraduate audience, accompanied by a variety of classroom activities.